The rising of the LGBT in Malaysia / Diyana Mastura Hesamuddin…[et al.] - Hesamuddin, Diyana Mastura; Azrin Harris,, Muhammad Alif Danial; Mohammad Din, Muhammad Muaz; Mohd Nor, Noraniqnuri (Faculty of Communication & Media Studies, 2019)
This research will discuss about an overview existing literature addressing lesbian, gay, bisexual and transgender (LGBT). This research was also aimed to study the factors of LGBT that commonly happens nowadays, to identify the effects and challenges faced by those who experienced, and to determine on how those people affecting with their surroundings. This research uses a qualitative method which includes a number of six respondents that aged among 19 to 23 which is experiencing or has experienced LGBT. This research using a deduction theory on this issue. The researchers point to ways that existing research approaches and theoretical stances benefit higher education practice to methodological and theoretical advancement is needed. Foremost the research also found that LGBT people faces negative perceptions from the society. Other than that, they involved in LGBT because of factors regarding their parents, friends, past life and others.